Design and synthesis of fluconazole/bile acid conjugate using click reaction - Pore, Vandana S.; Aher, Nilkanth G.; Kumar, Manish; Shukla, Praveen K. (Tetrahedron, 2006)
Novel fluconazole/bile acid conjugates were designed and their regioselective synthesis was achieved in very high yield via Cu(I) catalyzed intermolecular 1,3-dipolar cycloaddition. These new molecules showed good antifungal activity against Candida species. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; Antifungal agent; bile acid; Click chemistry; fluconazole/bile acid conjugate